Clinical Reasoning Behind Antibiotic Use in PICUs: A Qualitative Study*. Issue 3 (March 2022) - Fontela, Patricia S.; Gaudreault, Josée; Dagenais, Maryse; Noël, Kim C.; Déragon, Alexandre; Lacroix, Jacques; Razack, Saleem; Rennick, Janet; Quach, Caroline; McNally, James D.; Carnevale, Franco A.
Abstract : OBJECTIVES: To describe the reasoning processes used by pediatric intensivists to make antibiotic-related decisions. DESIGN: Grounded theory qualitative study. SETTING: Three Canadian university-affiliated tertiary medical, surgical, and cardiac PICUs. PATIENTS: Twenty-one PICU physicians. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We conducted field observation during morning rounds followed by semistructured interviews with participants to examine the clinical reasoning behind antibiotic-related decisions (starting/stopping antibiotics, or treatment duration) made for patients with a suspected/proven bacterial infection. We used a grounded theory approach for data collection and analysis. Thematic saturation was reached after 21 interviews. Of the 21 participants, 10 (48%) were female, 15 (71%) were PICU attending staff, and 10 (48%) had greater than 10 years in clinical practice. Initial clinical reasoning involves using an analytical approach to determine the likelihood of bacterial infection. In case of uncertainty, an assessment of patient safety is performed, which partly overlaps with the use of intuitive clinical reasoning. Finally, if uncertainty remains, physicians tend to consult infectious diseases experts. Factors that override this clinical reasoning process include disease severity, pressure from consultants, and the tendency to continue antibiotic treatment initiated by colleagues. CONCLUSIONS: Antibiotic-related decisions for critically ill children are complex, and pediatric intensivists use several clinical reasoning strategies to decrease the uncertainty around the bacterial etiology of infections. However, disease severity and patient safety concerns may overrule decisions based on clinical evidence and lead to antibiotic use. Several cognitive biases were identified in the clinical reasoning processes.